The reconciliation of the fundamentals of Islamic law Al-Muwāfaqāt fi Usūl al-Sharaī'a - Al-Shatibi, Ibrahim Ibn (Garnet Publishing Limited, 2011)
The Reconciliation of the Fundamentals of Islamic Law is an innovation in Islamic jurisprudence for it was for the first time that the objectives of shari'a were addressed, as they are in this book